VD_FINDINFO Jug / 2018 / 180 vom 31. Mai 2018 - VD Tribunal cantonal (2018)
IRRESPONSABILITÉ, PARTIE CIVILE, TRAITEMENTEN GÉNÉRAL | 126 al. 1 CP, 126 al. 2 CP, 129 CP, 144 al. 1 CP, 172ter CP, 186 CP, 22 ad 111 CP, 59 CP